Validation of microsatellite markers for assisted selection of soybean resistance to cyst nematode races 3 and 14 - Silva, Marcia Flores da; Schuster, Ivan; Silva, João Flávio Veloso da; Ferreira, Adésio; Barros, Everaldo Gonçalves de; Moreira, Maurilio Alves (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to validate microsatellite markers associated with resistance to soybean cyst nematode (Heterodera glycines Ichinohe) races 3 and 14, in soybean (Glycine max L.) genotypes, for use in marker-assisted selection (MAS) programs. Microsatellites of soybean linkage groups A2, D2 and G were tested in two populations, and their selection efficiencies were determined. The populations were 65 F2:3 families from Msoy8001 (resistant) x Conquista (susceptible) cross, and 66 F2:3 families of S5995 (resistant) x Renascença (susceptible) cross, evaluated for resistance to races 3 and 14, respectively. Families with female index up to 30% were considered moderately resistant. Markers of A2 and G linkage groups were associated with resistance to race 3. Markers Satt309 and GMENOD2B explained the greatest proportion of phenotypic variance in the different groups. The combinations Satt309+GMENOD2B and Satt309+Satt187 presented 100% selection efficiency. Resistance to race 14 was associated with markers of G linkage group, and selection efficiency in the Satt309+Satt356 combination was 100%. The selection differential obtained by phenotypic and marker assisted selection showed that both can result in similar gains.